IMPLEMENTASI SYIRKAH AL-INAN PADA MODEL KEMITRAAN PRODUKSI BENIH PADI DALAM PERSPEKTIF EKONOMI SYARIAH (STUDI DI PT PERSADA AGRO SEJATI) - Mohammad Farrohana Nasrulloh; Miftah Farid Imansyah; Eiry Zafirgi Prasetya; Mohammad Saiful Rifai (JSE: Jurnal Sharia Economica, 2026)
Partnerships in the agricultural sector are one of the strategies used to increase the productivity and quality of agricultural products, including in the production of hybrid rice seeds. From a sharia economic perspective, partnership practices need to be implemented based on the principles of justice, transparency, and cooperation in accordance with sharia contracts. This study aims to analyze the partnership model for rice seed production at PT Persada Agro Sejati and examine the implementation of syirkah al-'inān in these collaborative practices from a sharia economic perspective. This study uses a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the partnership model implemented by PT Persada Agro Sejati has characteristics close to the syirkah al-'inān contract because there are contributions of capital, production facilities, labor, and profit sharing based on an agreement between the company and farmers. This partnership practice generally reflects the principles of cooperation in sharia economics. However, there are still several aspects that need attention, especially regarding the risk-sharing mechanism, and the balance of bargaining power between the company and farmers. Therefore, strengthening the contractual aspects and clarity of the division of responsibilities is necessary so that partnership practices can be more in line with Islamic economic principles.